Decentralizing Economic Power in Ukraine: Institutional Mechanism, Current Trends, and Fiscal Aspects in the Sustainability Context - Lomachynska, I. A.; Churkina, I. YE. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2026)
This article reveals the processes of transformation of economic power in the conditions of decentralization in Ukraine, with elaborating on the institutional mechanism for its implementation in the sustainability and socio-economic welfare context. The decentralization of economic power is defined as a systematic redistribution of powers, resources, assets, and responsibility across management levels based on orderly measures, decisions, and the establishment of "rules of the game." Decentralization entails not only the formal redistribution of authority but also the creation of real conditions and institutional capacity for independent and effective decision-making. Consequently, the decentralization of economic power constitutes a vital tool for enhancing management adaptability to local needs and development specifics of individual territories. The institutional mechanism of economic power decentralization is defined as a holistic system of norms, organizational structures, and financial instruments that regulate interactions between economic entities. The key components of this mechanism are proposed. It is demonstrated that the institutional mechanism evolves from a simple redistribution of budget flows toward a complex system of incentives, enabling a transition from "resource allocation"" to "development management" within a specific territory. A matrix of institutional capacity for territorial communities is proposed as a comprehensive tool to assess a community’s ability to independently ensure sustainable development and socio-economic well-being under decentralization. Although the symmetric model was found to dominate in the economic decentralization in Ukraine, further development of the local government system should primarily be based on an adaptive (asymmetric) model. Fiscal decentralization was proved to remain the cornerstone among other types of decentralization: financial, market, administrative, and economic. Significant challenges and risks of economic decentralization in Ukraine were identified. Key areas for the further transformation of its institutional mechanism are substantiated, with emphasis on sustainable development and socio-economic growth. Technological modernization, digital transformation, integration with Sustainable Development Goals, energy decentralization, inclusion, and security are proposed as integral elements of this process.